2012
DOI: 10.1590/s1806-83242012005000018
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with dental caries in the primary dentition of children with cerebral palsy

Abstract: The aim of this study was to investigate factors associated with caries experience in the primary dentition of one-to five-year-old children with cerebral palsy. A total of 266 dental records were examined, and caries experience was measured by dmft. The following variables were also analyzed: gender, oral hygiene, history of gastroesophageal reflux, use of medications for gastroesophageal reflux, gingival status, sugar intake and reports of polyuria, excessive thirst and xerostomia. For analysis purposes, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
2
9

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 24 publications
3
29
2
9
Order By: Relevance
“…Contrary to our findings, Nelsen in case control study in Denmark showed that the caries rate of the CP-group was significantly lower than that of control group [35] a study in Brazil, the author mentioned that the children evaluated were not representative to all children with CP, but only of those who look for treatment in a reference center and they may possess better oral health due to enhanced parental attention and/or fewer difficulties in controlling oral conditions [36].…”
Section: Caries Prevalence In Children With Cpcontrasting
confidence: 99%
“…Contrary to our findings, Nelsen in case control study in Denmark showed that the caries rate of the CP-group was significantly lower than that of control group [35] a study in Brazil, the author mentioned that the children evaluated were not representative to all children with CP, but only of those who look for treatment in a reference center and they may possess better oral health due to enhanced parental attention and/or fewer difficulties in controlling oral conditions [36].…”
Section: Caries Prevalence In Children With Cpcontrasting
confidence: 99%
“…The results showed that gingivitis is associated with poor oral hygiene, as demonstrated in previous studies [9,10], and that there is a biological gradient for the oral hygiene variable in individuals with developmental disabilities similar to that for dental caries [17]. Another study did not show this association [7].…”
Section: Discussionsupporting
confidence: 52%
“…11 Performing effective oral hygiene is the main method for preventing this disease via the disorganization of the dental biofilm, which when colonized by cariogenic bacteria, acidify the environment through the decomposition of the substrate, causing the demineralization of the enamel and consequent progression of the process to the dentin and pulp. 12 Some factors are described in the literature as responsible for unsatisfactory oral hygiene in patients with CP. Highlighted among them are the level of motor skill necessary to perform oral hygiene effectively;…”
Section: Resultsmentioning
confidence: 99%